TEKNOLOGI ENERGI SURYA SEBAGAI SUMBER ENERGI ALTERNATIF DALAM PROSES ELEKTROPLATING - Warsono, Warsono; Maulana, Irfan; Rawati, Widya Yeni; Sunardi, Sunardi; Solehudin, Agus (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
The rapid development of technology today demands the utilization of renewable energy sources, one of which is solar energy. As a sustainable energy source, sunlight has great potential due to its abundant and unlimited availability. Therefore, solar energy can be utilized in Solar Power Generation Systems (PLTS) to meet the electrical needs of various applications. This study discusses the design of a PLTS system as a potential energy source for an electroplating device. The system employs a 100 Wp solar panel and a 12 V 20 Ah battery as an energy storage medium. Based on the test results, the minimum power output was 51 W at an irradiation level of 650 W/m², while the maximum power output reached 107 W at an irradiation level of 804 W/m². Additionally, the heating element in the electroplating system produced a maximum temperature of 63.7 °C. These results indicate that the designed PLTS system is capable of effectively supplying the required energy for the electroplating process. Keywords: Renewable energy, electroplating, solar power